Baseline factors predicting change from the initial DMARD treatment during the first 2 years of rheumatoid arthritis: experience in the ERAN inception cohort - McWilliams, Daniel F.; Kiely, Patrick D.W.; Young, Adam; Walsh, David A. (BioMed Central, 2013)
Background Outcomes in early Rheumatoid Arthritis (RA) may be improved by rapidly establishing a stable and effective disease modifying anti-rheumatic drug (DMARD) treatment regimen. We aimed to investigate whether baseline factors and initial treatment strategies are associated with changes to the first DMARD treatment, due to either Lack of Efficacy (LoE) or Adverse Drug Reaction (ADR) within 2 years of presentation.